Analysis of Occupational Psychological Factors Related to Burnout among Textile Workers in a Textile Manufacturing Company in Semarang - Ayu Prima Kartika; Jihan Faradisha; Jordan Syah Gustav; Warda Yussy Rha; Rizqy Kartika Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
Occupational psychological factors comprising interpersonal relationships, career development, role demands, and organizational climate play a pivotal role in shaping employee well-being and mitigating burnout in industrial settings. Burnout, characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, poses substantial risks to productivity and mental health, particularly among textile manufacturing workers who often face high physical demands, repetitive tasks, long working hours, and strict production targets. This study examined the associations between key occupational psychological factors and burnout among 54 textile workers in a textile manufacturing company in Semarang, Indonesia. A cross-sectional design was employed, with data collected using structured questionnaires and analyzed through Chi-Square tests. Results revealed significant associations between all examined factors and burnout: interpersonal relationships (p = 0,000), career development (p = 0,000), role demands (p = 0,011), and organizational climate (p = 0,009). These findings highlight the critical importance of fostering supportive interpersonal relationships, transparent career development opportunities, balanced role expectations, and a positive organizational climate to prevent burnout and enhance occupational health and performance.